Cold wind - Box, C. J. (New York : G. P. Putnam's Sons, 2011)
When Earl Alden is found dead, dangling from a wind turbine, it's his wife, Missy, who is arrested. Unfortunately for Joe Pickett, Missy is his mother-in- law, a woman he dislikes heartily, and now he doesn't know what to do --especially when the early signs point to her being guilty as sin. But then things happen to make Joe wonder: Is Earl's death what it appears to be? Is Missy being set up?
Keywords: Pickett, Joe (Fictitious character) -- Fiction; Game wardens -- Fiction; Mothers-in-law -- Fiction; Murder -- Investigation -- Fiction; Wyoming -- Fiction; Detective and mystery fiction